2010
DOI: 10.1073/pnas.1005889107
|View full text |Cite
|
Sign up to set email alerts
|

Interheme electron tunneling in cytochrome c oxidase

Abstract: Cytochrome c oxidase (CcO) is the terminal enzyme of the respiratory chain that catalyzes respiratory reduction of dioxygen (O 2 ) to water in all eukaryotes and many aerobic bacteria. CcO, and its homologs among the heme-copper oxidases, has an active site composed of an oxygen-binding heme and a copper center in the vicinity, plus another heme group that donates electrons to this site. In most oxidoreduction enzymes, electron transfer (eT) takes place by quantum-mechanical electron tunneling. Here we show by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
32
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 71 publications
4
32
1
Order By: Relevance
“…15,105 On the other hand, it is somewhat larger than what as been calculated for cytochromes and iron-sulphur proteins metalloproteins (38-75 kJ/mol for the oxidation of the isolated cofactor) 27,107,108 and appreciably larger than what has been obtained for intramolecular electron transfer in cytochrome c oxidase and the photosynthetic reaction centre (7-32 kJ/mol). 18,25 This is partly owing to the relative larger inner-sphere RE for copper sites than for cytochromes, partly to the presence of many charged groups around the Cu sites, needed to neutralise the large positive charge of the trinuclear T23 cluster with its neutral His ligands. Moreover, it is likely that our calculations with a nonpolarisable force field may overestimate the RE by ~35 %, 15,105,109 (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…15,105 On the other hand, it is somewhat larger than what as been calculated for cytochromes and iron-sulphur proteins metalloproteins (38-75 kJ/mol for the oxidation of the isolated cofactor) 27,107,108 and appreciably larger than what has been obtained for intramolecular electron transfer in cytochrome c oxidase and the photosynthetic reaction centre (7-32 kJ/mol). 18,25 This is partly owing to the relative larger inner-sphere RE for copper sites than for cytochromes, partly to the presence of many charged groups around the Cu sites, needed to neutralise the large positive charge of the trinuclear T23 cluster with its neutral His ligands. Moreover, it is likely that our calculations with a nonpolarisable force field may overestimate the RE by ~35 %, 15,105,109 (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…It has been used in several studies. 16,17,18,19,20,21,22,23,24,25 Several other groups have developed extensions to this theory, as well as other methods to calculate the RE at various levels of theory, including MM, QM/MM, and QM. 20,21,23,26 In particular, it has been shown that the RE in a protein can be estimated from QM or QM/MM calculations on snapshots from classical MD simulations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…D op is approximately 4 for the interior of a protein [88], the radius of the active site is 4 Å , and the radius of the electrondonating heme is 4.5 Å (according to the structure from [37]). The distance between the active site and the donating heme was estimated to be 9.6 Å (the distance between the two iron centers).…”
Section: Kinetic Barrier Calculationmentioning
confidence: 99%
“…The low barrier was a consequence of a low reorganization energy (0.57 eV) due to the hydrophobic environment of the protein at short range and the membrane at long range. This article discussed some discrepancies with a previously published paper reporting a very low reorganization energy (0.2 eV) on the same ET [58], highlighting the influence of computational set-ups when estimating reorganization energies from MD simulations.…”
Section: Classical Approaches Qm + MMmentioning
confidence: 77%